Investigation on Common Chronic Non-Communicable Diseases and Epidemiological Characteristics of Forsaken Elders Over 60 Years Old in Rural Areas of Datong, China - Sun Y; Liu CJ; Zhang N; Yang D; Ma C; Zhang X (Dove Medical Press, 2024)
Yongsheng Sun,1 ChengJiang Liu,2 Nianping Zhang,3 Debing Yang,4 Cungen Ma,5 Xi Zhang61Department of Neurology and Psychiatry, Medical College of Shanxi Datong University, Datong, 037009, People’s Republic of China; 2Department of General Medicine, Affiliated Anqing First People’s Hospital of Anhui Medical University, Anhui, 246000, People’s Republic of China; 3Department of Internal Medicine, Medical College of Shanxi Datong University, Datong, 037009, People’s Republic of China; 4Department of Anatomy, Medical College of Shanxi Datong University, Datong, 037009, People’s Republic of China; 5Neurobiology Research Center, Shanxi University of Traditional Chinese Medicine, Jinzhong, 030619, People’s Republic of China; 6Department of Neurology, Second Medical Center, General Hospital of the Chinese People’s Liberation Army, Beijing, 100000, People’s Republic of ChinaCorrespondence: Cungen Ma; Xi Zhang, Email macungen2001@163.com; zhangxiplagh@sina.comObjective: The common chronic non-communicable diseases and epidemiological characteristics of the forsaken elders over 60 in Guangling and Tianzhen were investigated and analyzed to provide reference for health resource allocation, hospital capacity establishing and health management of the forsaken elders in county-level regions.Materials and Methods: The data of 10,331 resident elderly over 60 in Guangling and Tianzhen of Datong Civil Affairs Bureau in the management system for disabled and semi-disabled elderly was collected. The gender, age, main diagnosis and coding of diseases, common chronic non-communicable diseases, and system diseases of the respondents were retrospectively analyzed.Results: The prevalence of the forsaken elders aged over 60 in Guangling and Tianzhen were different. Hypertension, arthritis, type 2 diabetes, hyperlipidemia and cerebral infarction are the top five common chronic non infectious diseases in Guangling, Tianzhen and the two counties. Among the top five common diseases in Guangling, Tianzhen and the two counties, arthritis or rheumatism, hypertension, diabetes or elevated blood sugar were found, which were different in the 60– 65, 66– 70, 71– 75 and 76– 80 groups, with the prevalence increasing with age. The top five diseases in Guangling, Tianzhen and the two counties were consistent, while the ranking changed slightly. The proportion of circulatory diseases, musculoskeletal diseases, connective tissue diseases and endocrine/nutritional and metabolic diseases in 60– 65, 66– 70 and 71– 75 groups increased with age, and was much higher than that in other groups.Conclusion: The prevalence and disease spectrum order of common chronic non-communicable diseases and systemic diseases in Guangling and Tianzhen are diverse, also in gender and age groups. As China’s county-level local administrative divisions have relatively independent administrative autonomy, medical and health resources can be better configured according to the information mined, accurately maintaining and promoting residents’ health. It is suggested to explore the disease management mechanism with county-level administrative divisions as database management units under the background of big data, so as to implement the interconnection and sharing of information among health-related departments in county-level regions.Keywords: chronic non-communicable diseases, system diseases, administrative division, disease spectrum, the forsaken elders